2009
DOI: 10.1080/07418820802119950
|View full text |Cite
|
Sign up to set email alerts
|

Race, Class or Neighborhood Context: Which Matters More in Measuring Satisfaction with Police?

Abstract: The primary purpose of this study is to assess the relative effects of race and class, at both individual and neighborhood levels, on public satisfaction with police. Using hierarchical linear modeling on 1,963 individuals nested within 66 neighborhoods, this study analyzes how individual-level variables, including race, class, age, gender, victimization and contact with police, and neighborhood-level factors, including racial composition, concentrated disadvantage, residential mobility and violent crime rate,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
284
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 258 publications
(299 citation statements)
references
References 67 publications
15
284
0
Order By: Relevance
“…But according to Dowler and Sparks (2008), the impact of race diminishes when perceptions of quality of life are considered. This finding is not quite congruous with that of Wu et al (2009), who assert that even a change in the social economic status does not produce any change in the trend. Wu et al argue that African Americans in higher socioeconomic communities continue to show lower satisfaction with the police than the White residents of the same communities.…”
Section: Literature Reviewmentioning
confidence: 41%
See 1 more Smart Citation
“…But according to Dowler and Sparks (2008), the impact of race diminishes when perceptions of quality of life are considered. This finding is not quite congruous with that of Wu et al (2009), who assert that even a change in the social economic status does not produce any change in the trend. Wu et al argue that African Americans in higher socioeconomic communities continue to show lower satisfaction with the police than the White residents of the same communities.…”
Section: Literature Reviewmentioning
confidence: 41%
“…demonstrated that different population groups express different levels of satisfaction with the police, with the more satisfied groups tending to show more positive attitudes toward the agents of law enforcement (Huebner, Schafer, & Bynum, 2004;Wu, Sun, & Triplett, 2009). Satisfaction is often based on preconceptions of the community members toward policing and preconceptions are influenced by the type of information the subject has been exposed to (Peirce, 1994).…”
mentioning
confidence: 99%
“…One consistent finding of previous research on perceptions of police is that younger individuals are more likely than their older counterparts to hold negative views of the police (Brown & Benedict, 2002;Correia, Reisig, & Lovrich, 1996;Frank, Brandl, Cullen, & Stichman, 1996;Hurst & Frank, 2000;Reisig & Correia, 1997;Vogel, 2011;Wu, Sun, & Triplett, 2009). In fact, age has been regarded as an important demographic variable in determining perceptions of police (Brown & Benedict, 2002;Cao, Frank, & Cullen, 1996;Webb & Marshall, 1995).…”
Section: Demographic Characteristicsmentioning
confidence: 61%
“…Prior research has continuously demonstrated that victims of crime are more likely to have less favorable perceptions of police (Brown & Benedict, 2002;Cao et al, 1996;Carter, 1985;Geistman & Smith, 2007;Hurst & Frank, 2000;Vogel, 2011;Wu et al, 2009) and to be more fearful of crime than those who have not been victimized (Yun, Kercher, & Swindell, 2010). These issues are particularly salient considering it has been suggested Hispanics are disproportionally victimized (e.g.…”
Section: Contextual Variablesmentioning
confidence: 92%
See 1 more Smart Citation